2016
DOI: 10.1186/s11689-016-9139-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced engagement with social stimuli in 6-month-old infants with later autism spectrum disorder: a longitudinal prospective study of infants at high familial risk

Abstract: BackgroundAutism spectrum disorder (ASD) is a neurodevelopmental disorder that affects more than 1 % of the population and close to 20 % of prospectively studied infants with an older sibling with ASD. Although significant progress has been made in characterizing the emergence of behavioral symptoms of ASD, far less is known about the underlying disruptions to early learning. Recent models suggest that core aspects of the causal path to ASD may only be apparent in early infancy. Here, we investigated social at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
134
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(159 citation statements)
references
References 105 publications
14
134
0
1
Order By: Relevance
“…From our review, among infants who go on to develop autism and toddlers with early autism symptoms, attention to faces and face parts begins to differ from neurotypical infants at 6 months of age (Chawarska et al, 2013, in press; Jones et al, 2015; Shic et al, 2014) with continued increasing atypicalities in the first years of life (Elsabbagh et al, 2009; 2012; 2013; Ozonoff et al, 2008; 2010; Rozga et al, 2011; Turner-Brown et al, 2013). Less attention to faces, and potentially increased attention to objects, will alter the types of information available to this perceptual learning system.…”
Section: A Failure Of Emergent Specialization In Asdmentioning
confidence: 96%
See 1 more Smart Citation
“…From our review, among infants who go on to develop autism and toddlers with early autism symptoms, attention to faces and face parts begins to differ from neurotypical infants at 6 months of age (Chawarska et al, 2013, in press; Jones et al, 2015; Shic et al, 2014) with continued increasing atypicalities in the first years of life (Elsabbagh et al, 2009; 2012; 2013; Ozonoff et al, 2008; 2010; Rozga et al, 2011; Turner-Brown et al, 2013). Less attention to faces, and potentially increased attention to objects, will alter the types of information available to this perceptual learning system.…”
Section: A Failure Of Emergent Specialization In Asdmentioning
confidence: 96%
“…In low risk and typically developing infants, attention to faces during habituation is often longer than to objects with significant decreases in time to habituation over the first year of life (Jones, Pascalis, Eacott, & Herbert, 2011; Jones et al, 2015; Reynolds et al, 2012; Robledo, Kolling, & Deák, 2010). In contrast, 6-month-old high risk infants who later met criteria for ASD (compared to high risk infants without early ASD) showed a significantly shorter peak look that was later in the habituation function, suggestive of disruptions to sensitization and deeper levels of processing (see Jones et al, 2015). Similarly, Chawarska et al (in press) also found that more attention to a speaker’s face at 6 months was associated with lower autism symptoms at 24 months.…”
Section: Early Developmentmentioning
confidence: 99%
“…To date, few reliable behavioral indicators of ASD have been consistently documented in infant siblings younger than 12 months, with most work reporting typical development for the first 6 months and subtle behavioral differences manifesting by the first birthday (for review, see Jones et al, 2014; Zwaigenbaum, Bryson, & Garon, 2013). Potential markers identified in the first 12 months include a decline in eye fixation, reduced social gaze, disrupted attention to social stimuli, enhanced visual search abilities, and increased atypical vocalizations (Chawarska, Macari, & Shic, 2013; Gliga, Bedford, Charman, Johnson, & Team, 2015; Jones et al, 2016; Jones & Klin, 2013). Specific temperament profiles, including reduced Positive Affect, increased Negative Affect, and difficulty regulating attention, have also been reported (Clifford et al, 2013; Filliter et al, 2015; Zwaigenbaum et al, 2005).…”
Section: Asd Symptoms In High-risk Infants With Non-syndromic Asdmentioning
confidence: 99%
“…Social attention has notably been identified as one of the earliest hallmark impairments in ASD with the promise of being a predictive diagnostic biomarker for ASD outcomes (Jones and Klin, 2013;Elsabbagh et al, 2014;Jones et al, 2016). These findings have now pushed the field to begin assessing and identifying effective behavioral and pharmacological treatments that can improve social functioning in ASD.…”
mentioning
confidence: 99%